Abandono familiar y autonomía de los adultos mayores del centro adulto mayor – Laredo, Trujillo 2021 - Martinez Perez, Brighitte Alexandra (2022)
The present thesis called Family abandonment and autonomy of older adults - Laredo, 2021, was addressed with the purpose of analyzing the influence of family abandonment on the autonomy of the elderly. Family abandonment omits the fulfillment of the basic needs of the elderly, at the same time the absence of affection and protection are key to generating autonomy in them, because considering them a family burden makes their feelings of value decrease, bringing with it the isolation and limitation of interpersonal relationships, which is why it is necessary to make them feel functional and useful to society. In the investigation, methods such as inductive - deductive, analytical, synthetic and statistical were used, in addition techniques and instruments were used for data collection, through the application of instruments and techniques to collect information, for which we worked with 50 older adults. In the elaboration of the discussion of results, it is manifested how the older adult does not feel the company of their relatives and the poor support in decision-making, generating the degradation of their autonomy so that the older adult does not feel functional. Much less active aging is promoted.